THE EFFECTIVENESS OF A BUTTERFLY STYLE SWIMMING SKILL LEARNING MODEL FOR JUNIOR HIGH - Yogi Yuliada; Widiastuti Widiastuti; Hernawan Hernawan (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The purpose of this study was to produce a butterfly style swimming learning model for junior high school students. The subjects in this research and development are students of Middle School. The research method used is the research and development model of Borg and Gall. Data collection techniques used are the results of expert validation and effectiveness testing through assessment instruments with t-test statistical data analysis. The results of research and development of a butterfly style swimming skill learning model for junior high school students shows that (1) the butterfly swimming skill learning model for junior high school students significantly improved the butterfly swimming skill of the students (2) Based on data analysis, the average value of pre-test 9.3750 and post-test average 17.6250 standard deviations of pretest 3.78721 and post-test 2.99305 average pretest and post-test 8.25000 and standard deviation 3.11119 value of t - 16.771 significance level 0.05 can be said that the Butterfly Style Swimming Skill Learning Model can improve butterfly style swimming skills and is effective to be applied in the learning process of butterfly style swimming skills for junior high school students.